1965
DOI: 10.1172/jci105311
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial pressure at high pulmonary flow.

Abstract: The relationship between pulmonary arterial pressure and pulmonary blood flow has been studied by a number of investigators in anesthetized animals (1), in man after pneumonectomy or unilateral pulmonary arterial occlusion (2, 3), and in normal man during exercise (4-7). With a few exceptions (1) these studies have agreed that doubling or trebling the pulmonary arterial flow does not produce a comparable increase of pulmonary arterial pressure. Sloan, Morris, Figley, and Lee (2) and Brofman (3) found in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The relationship between blood flow, vas cular pressures and resistances in the lung has been reported by several investigators [5][6][7], In the adult lung, flow can be increased three fold before any appreciable change in pulmo nary artery pressure is detected; however, when the lung is already fully recruited, in creases in blood flow result in large increases in pulmonary artery and venous pressures [8], When the total vascular surface area is re duced, an increase in flow will also markedly increase vascular pressures in the lung [ IV collagen, laminin, heparin sulfate, proteoglycansand clastin. Type-IV collagen is the ele ment in basement membranes which imparts strength to it.…”
Section: Discussionmentioning
confidence: 87%
“…The relationship between blood flow, vas cular pressures and resistances in the lung has been reported by several investigators [5][6][7], In the adult lung, flow can be increased three fold before any appreciable change in pulmo nary artery pressure is detected; however, when the lung is already fully recruited, in creases in blood flow result in large increases in pulmonary artery and venous pressures [8], When the total vascular surface area is re duced, an increase in flow will also markedly increase vascular pressures in the lung [ IV collagen, laminin, heparin sulfate, proteoglycansand clastin. Type-IV collagen is the ele ment in basement membranes which imparts strength to it.…”
Section: Discussionmentioning
confidence: 87%
“…A similar sharp rise in Ppa m at flows above 350 % of normal was reported a few years later in isolated perfused lungs (120). However, subsequent studies repeatedly reported a linear increase in Ppa m as a function of flow in isolated perfused lungs (59,236) as well as in intact human beings studied using the unilateral balloon occlusion technique (to double the flow in the contralateral lung) and/or exercise (18,44). There has been a recent report of a “take-off” pattern of Ppa m -Q relationships in normal subjects at exercise (216) reminiscent of the pioneering work of Cournand.…”
Section: Pulmonary Hemodynamics At Exercise In Healthy Humansmentioning
confidence: 99%
“…The lobe was perfused by means of a roller pump (model 3500, Sarns, Inc., Ann Arbor, Mich.) and the pumping rate was adjusted so that mean pressures in the lobar artery and main pulmonary artery were similar. The pumping rate was 293±12 ml/min (mean± SE, n = 20) 30, 100, and 300 Ag. All doses were administered in a random order and enough time was permitted between injections for hemodynamic variables to return to base-line levels.…”
Section: Introductionmentioning
confidence: 99%